Chinese Consumers' Purchase Intentions for Luxury Clothing: A Comparison between Luxury Consumers and Non-Luxury Consumers. Issue 5 (20th October 2018) - Zhang, Lini; Cude, Brenda J.
ABSTRACT: This study fills the literature gap by examining whether there are significant differences between the luxury clothing purchase intentions of luxury vs. non-luxury Chinese consumers and comparing the influence of the major factors that influence luxury clothing purchase intentions for luxury and non-luxury Chinese consumers. A total of 452 Chinese luxury clothing consumers and 236 Chinese non-luxury clothing consumers participated in the survey of this study. Using t-test, ANCOVA, and regression analyses, this study finds that there are significant distinctions between Chinese luxury consumers' and non-luxury consumers' purchase intentions for luxury clothing. The findings also show that significant distinctions exist between the factors that influence Chinese luxury consumers' and non-luxury consumers' purchase intentions. This study not only provides researchers with a better understanding of luxury consumers and non-luxury consumers in their purchase intentions for luxury goods but also provides luxury goods manufacturers and retailers with important implications to develop effective marketing strategies in the Chinese luxury goods market.